The profitability and management of the Norwegian Red King Crab (Paralithodes Camtschaticus) fishery - Wessel, Kari (Universitetet i Tromsø, 2004)
The Red King Crab and the consequences of its introduction to the Barents Sea and the North-Norwegian coast has been a source for research in many directions for several years. There has not been much financial research, despite the fact that the Red King Crab is a highly valuable nutritional species which gives it a highly economically value. In this thesis I look into the profitability for the vessels participating in the Norwegian Red King Crab fishery and look upon the challenges which the Norwegian Government faces when managing the Red King Crab. I look into different scenarios for the prevention of the further spread of the Red King Crab to the west is put forward. By using financial analysis and statistical analysis I analyse accounts for vessels fishing Red King Crab and compare them with accounts for vessels with similar sizes and fishing methods fishing in the same area, but not fishing for Red King Crab. My analysing is done for the years 2001 and 2002. After making the different analysis I conclude that the smaller vessels fishing Red King Crab have considerable higher profitability than the similar sized vessels not fishing Red King Crab. For the larger vessels I can not conclude that the Red King Crab fishing vessels profitability is higher than the vessels not fishing for Red King Crab. Fixed quotas equal for all vessels regardless of vessel size and the trouble with unscheduled secondary catch of Red King Crab in other fisheries might be a reason why larger vessels don’t benefit from the Red King Crab fishery as smaller vessels do. I look into the future management of the Red King Crab west of longitude 26º East, which is the western border where the Norwegian and Russian government has agreed to make effort to prevent the Red King Crab to spread further west. There are introduced different scenarios for how to prevent the Red King Crab to spread further west. I have looked into some consequences for some scenarios introduced by the Norwegian Minister of Fisheries like free access to fish in the ...